Reaching Outside the Comfort Zone: Realising the FCTC's Potential for Public Health Governance and Regulation in the European Union; Comment on "The Legal Strength of International Health Instruments - What It Brings to Global Health Governance?" - Florence Berteletti (Kerman University of Medical Sciences, 2018)
In their paper, Nikogosian and Kickbusch show how the effects of the adoption by the World Health Organization (WHO) of the Framework Convention on Tobacco Control (WHO FCTC) and its first Protocol extend beyond tobacco control and contribute to public health governance more broadly, by revealing new processes, institutions and instruments. While there are certainly good reasons to be optimistic about the impact of these instruments in the public health sphere, the experience of the FCTC's implementation in the context of the European Union (EU) shows that further efforts are still necessary for its full potential to be realised. Indeed, one of the main hurdles to the FCTC's success so far has been the difficulty in developing and maintaining comprehensive multisectoral measures and involving sectors beyond the sphere of public health.